Gastronomía ancestral y su contribución al desarrollo turístico en el cantón Quevedo Provincia de Los Ríos, año 2021 - Castro Leal, Veronica Lucrecia (2021)
This work was carried out in the Quevedo canton, Los Ríos province, currently known as the River City, which is in an unprecedented tourist boom, due to the growth of tourist places and attractions in favor of promoting tourism in the city of Quevedo. It is also a city examined by national tourists due to its delicious and varied cuisine, based mainly on seafood from the river and products from the Ecuadorian coast; The general objective of this study is to determine the contribution of ancestral gastronomy in tourism development, its main interest being to publicize its contribution and its reinvention for progress, becoming a subject for the development of future projects in the tourism field. The proposal of this investigative work is to know how ancestral gastronomy contributes to the tourist development of the canton and therefore to create and develop gastronomic programs that help establishments to promote ancestral food.